Dimensions of the Early Islamic Use of Al-Ruqyah Al-Islāmiyyah: Insights from Maḥmūd Nāẓim Al-Nasīmī - Muhammad Akmalludin Mohd Hamdan; Ahmad Salahuddin M Azizan; Syed Mohamad Zainudin Bichk Koyak (Universiti Sains Islam Malaysia, 2026)
Indexed by MyCite